2015
DOI: 10.1007/s00445-015-0983-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal state and implications for eruptive styles of the intra-Plinian and climactic ignimbrites of the 4.6 ka Fogo A eruption sequence, São Miguel, Azores

Abstract: The 4.6 ka Fogo A Plinian eruption was a caldera-forming volcanic event on São Miguel Island, Azores. The deposit succession is very complex, composed of a thick trachytic Plinian fallout deposit interstratified with two intra-Plinian ignimbrites (named “pink ignimbrite” and “black ignimbrite” sequentially). The succession ends with a main ignimbrite (named “dark brown ignimbrite”), which represents the deposit of complete collapse of the eruption column and the end of the eruption. In this work, emplacement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…We therefore trust the values obtained (cf. Pensa et al, 2015b) that need, though, to be addressed for their variations in such a very limited area. These variations partly reflect the stratigraphy, where the three sites sampled in lower unit EU2/3pf, VP4, VP6 and VP8, show the lowest T dep values (Fig.…”
Section: Interpretation Of Trm Datamentioning
confidence: 99%
“…We therefore trust the values obtained (cf. Pensa et al, 2015b) that need, though, to be addressed for their variations in such a very limited area. These variations partly reflect the stratigraphy, where the three sites sampled in lower unit EU2/3pf, VP4, VP6 and VP8, show the lowest T dep values (Fig.…”
Section: Interpretation Of Trm Datamentioning
confidence: 99%
“…(e.g. Moore and Rubin 1991;Wallenstein 1999;Pensa et al 2015), but its age is generally reported as ~5 ka. Although the deposit is not genetically related to Furnas, it is well known and easily identified and, in the absence of well-exposed deposits relating to the second caldera-forming event at Furnas (~12,000 14 C y B.P.…”
Section: Furnas Eruptive Historymentioning
confidence: 99%
“…The second set of charcoal samples comes from PDC deposits of the 4.6 ka Plinian eruption of Fogo volcano (Azores), known as Fogo A eruption [21,45]. Fogo volcano, located at the center of São Miguel Island, is one and the largest of the three active Quaternary volcanoes composing the Azorean islands.…”
Section: Geological Setting and Materialsmentioning
confidence: 99%
“…In this work, for the first time, we aim to investigate the evolution of Raman spectra at relatively low temperatures (mainly between 250 and 600 • C), more relevant for PDCs flow and emplacement conditions [21,45]. With this purpose, based on already existing charcoal reflectance datasets, we selected charred wood samples from three different eruptions, (Figure 1a): the 2015 Volcan de Colima eruption, (Mexico), the 2015 Calbuco Volcano eruption (Chile) and the 4.6 ka Fogo Volcano eruption (Azores, Portugal).…”
Section: Introductionmentioning
confidence: 99%